Contemporary collage in modern art - Busch, Dennis, ....-; Klanten, Robert, 1964- (Berlin : Die Gestalten Verlag, 2016)
Bringing disparate images and items together, collage transcends the boundaries between artistic disciplines. The traditionally analog technique has its roots in surrealism and Dada. Having effortlessly evolved to embrace digital tools and the combinatory freedom that they offer, collage is now making a promising comeback.0'The Age of Collage Vol. 2' presents the work of more than 80 collage artists - from established names including John Baldessari and Richard Prince to up-and-coming talents such as Lola Dupré. A follow-up to 'The Age of Collage', the book is a comprehensive showcase of the surprising diversity of this genre today.
Keywords: Collage; Collage